Preliminary study of the airborne pollen in the atmosphere of Puerto Ayora (Galapagos Islands, Ecuador) - Picornell Rodríguez, Antonio; Trigo-Pérez, María del Mar; Recio-Criado, María Marta; Jaramillo Díaz, Patricia (De Linares C. & Belmonte J, 2017)
Galapagos is an archipelago of volcanic islands located 972 km west from the continental Ecuador. They were declared by the UNESCO as a World Heritage Site and Biosphere Reserve due to their singular environmental value, where a third part of the native plants are endemic to this archipelago (Jaramillo et al., 2011). In spite of the numerous scientific studies carried out in Galapagos, there are not any aerobiological samplings being performed currently. The main objectives of this study were to install a pollen trap for detecting the presence of pollen in the atmosphere of Puerto Ayora (Santa Cruz, Galapagos Islands) and qualitatively identify the different pollen types detected during the studied period. A Durham (1946) gravimetric pollen trap was modified to turn it into a passive impact pollen trap based on Pla Dalmau (1957) modifications. It was placed on the roof of the Galapagos National School (Puerto Ayora, Santa Cruz Island) at a height of 15m above ground level. The samples were obtained by using silicone fluid as adhesive substance and glycerine gelatine as mounting mean. The pollen grains were counted in a surface of 14 x 48 mm in each sample. The pollen types were identified with the aid of the pollen guide of the Galapagos Island by Jaramillo & Trigo (2011) and the Charles Darwin Foundation pollen bank. Pollen types of endemic plants such as Darwiniothamnus sp., Passiflora foetida var. galapagensis Killip, Justicia galapagana Lindau and Castela galapageia Hook. f. were detected together with those of other native and introduced species. A high diversity of pollen types was detected, reflecting the particular vegetation of the island. This preliminary aerobiological information can be used as precedent for further studies on the pollination of native and introduced species of the Galapagos Islands, as well as for detecting possible allergic diseases in the population.
Keywords: Botánica; Palinología; Biología Vegetal; Aerobiology; Pollen; Allergy; Galapagos Islands